Surveillance of bacterial resistance in health institutions in the city of Hermosillo, Sonora, Mexico - Enrique Bolado-Martínez; Andrea Roxana Nevárez López; Maria del Carmen Candia-Plata; Grupo de Vigilancia de la Resistencia Bacteriana Hospitales de la Ciudad de Hermosillo, Sonora (Salud Pública de México, 2018)
[Not available]